Tenderize Chicken Breast Meat by Using Different Methods of Curing - Al-Hajo, N.A. Nadia (Pakistan Journal of Nutrition, 2009)
The aim of this study is tenderizing breast spent hens meat by using cheap local materials such us (bitter orange juice, vinegar, salt and sugar for (1, 2 and 3) h, distill water is used (T1) in curing to make it as standard. Bitter orange juice (acidity of 1.5) (T2), vinegar (acidity of 7) (T3), table salt (2%) (T4) and sugar (2%) (T5) were used. The processed meat was investigate the influence of the type of treatment and the periods of storing and submersion on the sensory properties and chemical qualities through estimating the percentage of moisture, volume of the released extract. A sensory properties evaluation of the qualities of flavor, juiciness, tenderness and overall acceptance was carried out. The following findings were obtained: The percentage of moisture increased significantly (p